Minat Gereja dalam Membangun Komunitas Remaja Pemuda Melalui Pemuridan [The Church's Interest in Building the Community of Youth and Young Adult Through Discipleship] - Yatmini Yatmini; Rio Pardede (Diligentia: Journal of Theology and Christian Education, 2022)
This study aims to see to what extent the church has an interest in building a youth community through discipleship. The method used in this research is descriptive research method. Collecting data by distributing questionnaires and making descriptions, descriptions in a systematic, factual, and accurate way about the facts, characteristics, and relationships between the phenomena being investigated. Based on the findings of the questionnaire distributed through google form, about the church's interest in building youth communities through discipleship: 1) not all churches have an interest in discipleship, 2) lack of leaders, affects the church's interest in making discipleship programs, 3) lack of discipleship materials affect the implementation discipleship, 4) the limitations of the leader to convey discipleship materials creatively and not monotonously.